Relapse prevention among Iranian people who smoke through cognitive behavioral intervention: application of Marlatt’s model - Shahnaz Hajisahneh; Sakineh Rakhshanderou; Yadollah Mehrabi; Emran Mohammad Razzaghi; Leili Mazar; Mohtasham Ghaffari (BMC Psychiatry)
Abstract Background Relapse is by far the most likely outcome of any smoking cessation attempt. The present study aimed to assess the effectiveness of cognitive-behavioral intervention based on Marlatt’s model on relapse prevention of people who smoke. Methods This interventional study was conducted among 265 people who smoke who referred to smoking cessation centers in Kurdistan province in Iran (intervention group = 129, control group = 136). The intervention group received cognitive behavioral therapy smoking cessation based on the Marlatt’s model for 8 sessions and each session was one hour weekly, and the control group received routine smoking cessation treatment trough 7 one-hour weekly sessions. The data were collected by using a researcher-made questionnaire. The follow-ups were performed immediately, 1 week and 3 months after the intervention. Results We found that 42.6% of the intervention group consumed more than 20 cigarettes daily before the intervention, reaching to 13.7% immediately, 10.2% one week and 6.2% three months after the intervention. There was a significant difference in the mean scores of internal and external high-risk situations, internal and external self-efficacy, coping skills, positive and negative outcome expectations, and abstinence violation effect between the intervention and control groups at immediately, one week, and three months after the intervention (P < 0.0001). A significant difference between the lapse and relapse rate in the intervention group compared to the control group immediately, one week and three months after the intervention was observed (P < 0.001). Conclusion Cognitive-behavioral intervention is effective in reducing cigarette smoking, high-risk situations of smoking, abstinence violation effect, positive outcome expectation of smoking lapse and relapse and increasing self-efficacy, coping skills, and quitting smoking.